Nature of Buyer–Supplier Relationship: Small Businesses in a Small City. (1st July 2017) - Murthy, Venkatesh; Paul, Bino
Abstract : If the proposition of Williamson that "highly standardized transactions are not apt to require a specialized governance structure" (1979, p. 248) is to be accepted, then a discrete transaction market between small business owners and their suppliers can be easily organized in the market. This view essentially nullifies the possibility of there being a relational transaction. In this backdrop, this research attempts to explore the small buyer–supplier relationship in the context of a small city. Keeping embeddedness (Granovetter, Am. J. Sociol ., 1985; 91: 481–510) as a theoretical foundation, we explore the social content in an apparently pure economic exchange. Although, earlier attempts (Khoja and Kauffman, J. Small Bus. Manag., 2012; 50: 20–40; Uzzi, Am. Socio. Rev., 1996; 61: 674–698) conformed to embeddedness in transactions between a buyer and a supplier among businesses of various sizes, they largely ignored very small‐size buyers and suppliers owing to the miniscule size of business transactions and less frequent interactions between buyers and suppliers. Based on the grounded theory approach (Strauss and Corbin, Basics of Qualitative Research‐Grounded Theory Procedures and Techniques, 1990), in this study, we conducted in‐depth interviews with 57 very small business owners to develop detailed narratives. These narratives were organized under four themes: Contractual relationship, Strategic information sharing, Caste as a proxy, and Trust Factor. The findings clearly indicate that small business owners foster continued relationships with their suppliers, owing to social conditioning factors.